Crispld2 is required for neural crest cell migration and cell viability during zebrafish craniofacial development. Issue 10 (5th September 2015) - Swindell, Eric C.; Yuan, Qiuping; Maili, Lorena E.; Tandon, Bhavna; Wagner, Daniel S.; Hecht, Jacqueline T.
Summary The CAP superfamily member, CRISPLD2, has previously been shown to be associated with nonsyndromic cleft lip and palate (NSCLP) in human populations and to be essential for normal craniofacial development in the zebrafish. Additionally, in rodent models, CRISPLD2 has been shown to play a role in normal lung and kidney development. However, the specific role of CRISPLD2 during these developmental processes has yet to be determined. In this study, it was demonstrated that Crispld2 protein localizes to the orofacial region of the zebrafish embryo and knockdown of crispld2 resulted in abnormal migration of neural crest cells (NCCs) during both early and late time points. An increase in cell death after crispld2 knockdown as well as an increase in apoptotic marker genes was also shown. This data suggests that Crispld2 modulates the migration, differentiation, and/or survival of NCCs during early craniofacial development. These results indicate an important role for Crispld2 in NCC migration during craniofacial development and suggests involvement of Crispld2 in cell viability during formation of the orofacies. genesis 53:660–667, 2015. © 2015 Wiley Periodicals, Inc.